1984
DOI: 10.1139/g84-069
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of four taxa of the Anopheles balabacensis complex using H-banding patterns in the sex chromosomes

Abstract: W~eowo, S., V. BAIMAI, and R. G. . Differentiation of four taxa of the Anopheles balabacensis complex using H-banding patterns in the sex chromosomes. Can. J . Genet. Cytol. 26: 425-429. Analyses of metaphase chromosomes of four taxa of the Anopheles balabncensis complex ( A . dirus A, B, and C, and A. takasagoensis) using the Hoechst 33258 staining technique have revealed remarkable differences in the fluorescence banding patterns of the sex chromosomes. These result from changes in the amount and distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Other studies of the Dirus and Leucosphyrus Complexes showed that they were groups of apparently isomorphic but reproductively distinct species. Discovery of most members of the Dirus Complex was achieved primarily with crossing studies, cytogenetics (chromosome banding patterns), allozyme data, DNA probes and DNA hybridization (Hii, 1984b; Wibowo et al ., 1984; Baimai et al ., 1987, 1988a; Panyim et al ., 1988; Green et al ., 1992; Audtho et al ., 1995). Cytogenetic studies on members of the Leucosphyrus Group in Thailand and peninsular Malaysia showed differences in the amount and distribution of heterochromatin in the sex chromosomes, suggesting that An.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies of the Dirus and Leucosphyrus Complexes showed that they were groups of apparently isomorphic but reproductively distinct species. Discovery of most members of the Dirus Complex was achieved primarily with crossing studies, cytogenetics (chromosome banding patterns), allozyme data, DNA probes and DNA hybridization (Hii, 1984b; Wibowo et al ., 1984; Baimai et al ., 1987, 1988a; Panyim et al ., 1988; Green et al ., 1992; Audtho et al ., 1995). Cytogenetic studies on members of the Leucosphyrus Group in Thailand and peninsular Malaysia showed differences in the amount and distribution of heterochromatin in the sex chromosomes, suggesting that An.…”
Section: Introductionmentioning
confidence: 99%
“…comprised at least four genetically distinct genetic species: these were designated An. dirus A, B, C and D (Baimai et al ., 1981, 1984; Hii, 1982; Wibowo et al ., 1984). Kanda et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations